Traditional Methods for Treatment and Management of Measles in Northern Nigeria: Medicinal plants and their molecular docking - Abdulrahman, Mahmoud Dogara; Bradosty, Sarwan W.; Hamad, Saber W.; Ibrahim, Muhammad Tukur; Lema, Abubakar Abdullahi; Sunusi, Namadi; Usman, Muhammad; Ashiru, Ibrahim; Ahmad, Nuraddeen Bello; Wada, Nuradeen; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2022)
Background: Measles is one of the major causes of death among young children worldwide. According to the World Health Organization, measles affects more than 20 million people globally each year, with around 17 millions of them being children. In Nigeria, traditional herbal medicine has long been employed to treat this disease. Methods: Purposive sampling was used with the aid of an open-ended interview guide, from March–December 2021. In addition, a literature search was carried out on the reported plants. Molecular docking-based virtual screening was employed to identify possible compounds with higher affinity to the target enzyme. Results: Twenty-four medicinal plants and three traditional methods were documented for the treatment and management of measles in Northern Nigeria. Cow dung and fermented Sorghum had the highest Fidelity Level at 100 %, respectively. Leaves were the most common plant part used for the treatment of measles, likely due to the presence of secondary metabolites. Decoction and oral application were the most effective methods of preparation and administration, respectively. The binding affinities of the investigated compounds ranged from -1.3 Kcal/mol to -9.3 Kcal/mol, respectively. From the molecular docking, Quinoline and Amyrin were identified to have the highest binding affinity of -9.3 Kcal/mol, respectively. Conclusion: This study adds to our understanding of the plants utilized by Northern Nigerians in the prevention and treatment of measles. These data may be used to further pharmacological research on these therapeutic plants, with a focus on safety, standardization, and effective dose. Keywords: African Medicinal Plant, Measles, Medicinal plants, Nigeria, In Silico